Implementación de Jardines de Conservación In Situ, en el Bosque Siempreverde Montano Bajo de la Cordillera Occidental de los Andes (bsbn04), en la Provincia de Cotopaxi-Cantón Pujili-Parroquia El Tingo-La Esperanza. (1400-2000 msnm) - Amaguaña Supe, Erika Maribel (2019)
The research aims to design an in-situ conservation garden in the Low montane forest of the western cordillera of the Andes in El Tingo parish, at the altitudinal floor from 1400 to 2000 meters above sea level. At this place, the floristic variety and diversity respect to the other altitudinal floors will be determined. For this purpose, an observation parcel of 200 m2 will be set; area limited with a rope and marking tape to achieve better visibility among the vegetation. Inside the parcel, all the specimens with a Breast Height Diameter – BHD, equal to or greater than 2.5 cm, will be measured, collected and identified. Using the AUTOCAD software, georeferenced position of each arboreal and shrubby species will be located considering the topographic conditions of the terrain. Within the investigation parameters as floristic composition, the current state of the forest and use of the identified species will be known; base information that the Technical University of Cotopaxi through the Germplasm Bank, will have the necessary tools and criteria for taking decisions regarding the management, conservation and recovery of the forest. Therefore, diagnosis regarding the execution of plans, programs and future projects can be implemented, aiming to change the lifestyle of populations next to the forest towards sustainable and bearable management of natural resources, where man and nature are in balance